Effect of Hydroxyapatite Coating in Combination with Physical Modifications on Microshear Bond Strength of Zirconia to Resin Cement - Faezeh Atri; Vanya Rasaie; Sakineh Nikzad Jamnani; Saba Mohammadi (International Journal of Dentistry)
Background. Zirconia has been used as a reliable core material in dental restorations for years; however, its bonding to resin cement is a matter of challenge. Physical, chemical, and combinations of these techniques have been investigated to boost the properties of zirconia surface bonding. The objective of this work was to evaluate the effect of hydroxyapatite coating as a chemical therapy in combination with physical modifications on the microshear bond strength of the resin cement over zirconia. Methods. In the present research, 60 sintered zirconia blocks (4 × 4 × 4 mm) were randomized into four groups of 15, including Al2O3 particle abrasion (group 1), HA coating (group 2), Al2O3 particle abrasion + HA coating (group 3), and Er, Cr: YSGG laser irradiation + HA coating (group 4). The microshear bond strength was determined by bonding the blocks to the resin cement. Results. The bond strengths (mean ± standard deviation) of modified zirconia surfaces were 16.93 ± 4.94 MPa, 16.14 ± 5.4 MPa, 19.4 ± 5.27 MPa, and 16.21 ± 3.7 MPa in groups 1–4, respectively. Test results of the ANOVA test revealed no significant difference regarding the bond strength values of zirconia surfaces to the resin cement between the studied preparation modalities (p>0.05). Conclusion. Observations from the present study showed that HA coating can be as effective as the air-borne particle abrasion technique in improving bond strength to zirconia surfaces. Moreover, sandblasting by an aluminum oxide or Er, Cr: YSGG laser irradiation prior to HA coating of zirconia showed no significant effect on the reinforcement of bond strength values when compared to HA coating alone. The clinic hydroxyapatite coating alone or in combination with physical treatments improves the bond strength of zirconia to resin cement.